1998
DOI: 10.1021/ac971141v
|View full text |Cite
|
Sign up to set email alerts
|

Method Translation and Retention Time Locking in Partition GC

Abstract: Method translation in gas chromatography (GC) is a variation of components (columns, carrier gases, detectors, etc.) and parameters (pressures, temperature programs, etc.) of a method in a way that maintains the peak elution pattern. The concept is based on the fact that the void time can be viewed as a universal time unit in GC; method translation is the scaling of the time axis of the temperature program relative to the void time. Method translation can be used to reduce analysis time, improve resolution, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 17 publications
2
92
0
3
Order By: Relevance
“…26 In the RTL method, the inlet pressure is adjusted to provide an identical retention time for the same compound in any system equipped with the same nominal column. This method applies constant pressure and only small deviations in column size and stationary phase loading parameters are tolerated; moreover, it cannot be used under constant flow-rate conditions.…”
Section: Retention Index Theoriesmentioning
confidence: 99%
“…26 In the RTL method, the inlet pressure is adjusted to provide an identical retention time for the same compound in any system equipped with the same nominal column. This method applies constant pressure and only small deviations in column size and stationary phase loading parameters are tolerated; moreover, it cannot be used under constant flow-rate conditions.…”
Section: Retention Index Theoriesmentioning
confidence: 99%
“…In terms of the temperature program, theoretical studies have shown that a rate of 108C per void time should be used in order to attain an optimum separation [25]. If this value is exceeded, the amount of time that the volatiles are partitioned in the stationary phase is not sufficient (capacity factors are reduced below a critical level) for satisfactory component resolution.…”
Section: Theory and Instrumental Requirementsmentioning
confidence: 99%
“…In the case of nonexcessively fast GC applications, less expensive scanning systems (i. e. quadrupole) may be used even for quantitative purposes [17]. In fact, ultimate generation quadrupole mass spectrometers (qMSs), operated in the full scan mode (the mass range window may be reduced, but spectral information could be lost), may generate up to [20][21][22][23][24][25] patibilities. The effectiveness of a rapid scanning quadrupole MS in a narrow-bore column fast GC analysis on menhaden oil FAMEs was shown by Mondello et al [44].…”
Section: Narrow-bore Columnsmentioning
confidence: 99%
“…Dans le cadre du screening par CPG-SM, les maintenances de routine (colonne coupée, installation d'une colonne neuve), entrainent un décalage des temps de rétention plus ou moins important. Pour pallier ce problème, Blumberg et Klee ont développé le concept de retention time locking (RTL) [9]. Il permet de rétablir les temps de réten-tion d'origine, décalés suite à une maintenance, par ajustement de la pression.…”
Section: Introductionunclassified